Anti‐consumption behavior: A meta‐analytic integration of attitude behavior context theory and well‐being theory. Issue 12 (8th November 2022) - Maseeh, Haroon Iqbal; Sangroya, Deepak; Jebarajakirthy, Charles; Adil, Mohd; Kaur, Jaspreet; Yadav, Miklesh P.; Saha, Raiswa
Abstract: Researchers have given considerable attention to investigate anti‐consumption behavior. However, empirical research tends to report somewhat erratic and inconsistent findings. Accordingly, the relationships between the antecedents, and the outcome variables of anti‐consumption behavior, such as consumer well‐being, remain unclear. Thus, to fill this void in the literature, this study integrates Attitude Behavior Context (ABC) theory and Well‐being theory into a meta‐analytic framework and synthesizes the extant literature on anti‐consumption to examine concrete relationships between the contextual and attitudinal variables, anti‐consumption behavior and consumer well‐being. The findings show that ecological concern, religiosity, mortality salience, and perceived behavioral control influence anti‐consumption attitudes and intention, whereas consumer well‐being is the outcome variable of anti‐consumption behavior. To investigate the possible reasons for the inconsistent findings, we performed a moderation analysis which suggests that country of study, product type, data collection period, research methods and sample type may cause inconsistencies in the findings. This meta‐analytic study contributes to the anti‐consumption literature. Practically, the findings provide guidelines to policymakers and societal organizations interested in promoting anti‐consumption.